2018
DOI: 10.2174/1875399x01811010069
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time to Visual Stimulus in Firefighters and Healthy Trained Subjects: A Preliminary Comparative Study

Abstract: Background: In order to stay safe, and to successfully complete their work, firefighters have to constantly assess and process large numbers of sensory stimuli and adapt to the inherent risks present in the working environment. Objective: The purposes of the present preliminary study were to analyse the speed of Reaction Time responses (RT) of Italian Firefighters and to compare their cognitive respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…We hypothesized that the "static" execution of the test did not reproduce the highly variable working conditions on where firefighters usually operate. Compared with our previous study [29], the new results demonstrated low value in both female and male recruits for MRT in all trial, but with a different trend for errors. Despite Morris et al [52] shown that RT can be impaired when wearing a weighted vest to simulate personal protective equipment while performing a simulated…”
Section: Plos Onecontrasting
confidence: 77%
See 2 more Smart Citations
“…We hypothesized that the "static" execution of the test did not reproduce the highly variable working conditions on where firefighters usually operate. Compared with our previous study [29], the new results demonstrated low value in both female and male recruits for MRT in all trial, but with a different trend for errors. Despite Morris et al [52] shown that RT can be impaired when wearing a weighted vest to simulate personal protective equipment while performing a simulated…”
Section: Plos Onecontrasting
confidence: 77%
“…Zhang et al [50] reported faster response time after a treadmill exercise in a heated chamber, while Hemmatjo et al [51] showed a faster RT (but with less correct responses) at the end of firefighting activities in a smoke-diving room. Previously, our group [29] found that firefighters made significantly more errors than no firefighters in basal condition, where the RT required was high, underlining a lower level of cognitive function. We hypothesized that the "static" execution of the test did not reproduce the highly variable working conditions on where firefighters usually operate.…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…e Fitlight Trainer ® (FitLight Sports Corp, Canada; available in Greece by Serinth ® ) is a wireless reaction system comprised of four LED lights controlled by a tablet computer. e lights have an inbuilt sensor which reacts proximity or touch and deactivates the light [13]. Four lights positioned on the floor were used as stimulus (Figure 1) and turning off the lights was done with feet.…”
Section: Methodsmentioning
confidence: 99%